Reviving a European Idea: Author’s Right of Withdrawal and the Right to Be Forgotten under the EU’s General Data Protection Regulation (GDPR) - Bak, Basak (SCRIPT-ed, 2022)
The right of withdrawal allows authors to unilaterally withdraw a copyright contract and retract copyrighted work to disassociate based on moral reasons. Although accepted in some European jurisdictions, the right of withdrawal is mainly theoretical due to the scarcity of case law resulting from its strict requirements. Therefore, it has been perceived as a concept without practical use. However, this right is underpinned by a significant and still valid European idea reflected by the EU’s General Data Protection Regulation, outlined in the data subject’s right to be forgotten. While the right of withdrawal and the right to be forgotten have different characteristics and goals, these two rights share the same reasoning, emphasising that the same European spirit is still alive and very much needed.